IMPROVING STUDENTSâ READING INTEREST AND PARTICIPATIONTHROUGH METACOGNITIVE STRATEGY - Suhaimi, Suhaimi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2017)
Lack of studentsâ interest and participation in learning reading at English Department of IAIN Kerinci were caused by two problems. First, low creativity, lack of participation, and low discipline of students in reading. Second, the teacherâs strategy used were lass variety and interactive. So, the students were easy to get bored and reluctant to read. To solve those problems, the researcher conducted the classroom action research by implementing Metacognitive Strategy with fabulous three strategies namely; planning, monitoring, and evaluating. The research results showed that the implementing of Metacognitive Strategy could stimulate students to be participated in reading. Besides that, this strategy increased the studentsâ interest in reading activities. Based on the result of observation analysis of students reaction, it was found that almost all of students were participated and interested in reading. Those data were also supported by the questionnaire result which was indicated that 80,55% students were interested in reading, and 75,94% students were participated in reading. In conclusion, Metacognitive Strategy could improve studentsâ interest and participation in reading English text at the third semester students English Department of IAIN Kerinci. Hopefully, the research result could be positive input for other researchers and teachers to conduct the research and teaching program, particularly on reading issue.